Implementasi model pemberdayaan masyarakat berbasis edukasi partisipatif dalam penguatan kapasitas sosial dan ekonomi lokal - Suyono Suyono; Indi Aunullah; Halimatus Sa’diyah (Nur Science Institute, 2026)
The goal of this community service project was to raise the socioeconomic standing of coastal communities whose restricted participation in development decision-making has limited their ability to become self-sufficient. The primary problem identified was low participation in educational programs that promote social and economic empowerment. The initiative adopted a participatory community empowerment approach, making the community the focal point of learning, planning, and execution. Capacity development was achieved through instructional interventions, needs mapping, group-based mentoring, and marine-based entrepreneurship training grounded in religious values and sustainable local practices. According to the findings, community involvement in cooperative fish farming has grown, there is greater collaboration between pesantren youth organizations, and small-scale seafood processing enterprises are using local marine resources. Additionally, the initiative increased public awareness of the shared social responsibility to promote local development. In conclusion, the participatory education-based empowerment model successfully enhanced community capacity and fostered long-term socioeconomic development.